Kajian Kebutuhan Dan Ketersediaan Sumber Air Spamdes Di Dusun Kaliapak, Banjarsari, Samigaluh, KulonProgo - Muhamad Hafidzudin Ichsan; Ani Hairani; Burhan Barid (Civil Engineering Department, Universitas Muhammadiyah Yogyakarta, 2022)
This research was conducted at SPAMDes (Sistem Penyediaan Air Minum Pedesaan) Tirta Lestari which is located in Kaliapak, Banjarsari, Samigaluh, Kulon Progo. This study discusses the water availability from SPAMDes Tirta Lestari for 10 years later. The purpose of this research to determine the capacity of customers that can be served with existing source water discharge and predict the final year that can be served with the growth of customers and existing source water discharge. This research method uses least square and geometric methods in predicting population growth. Analysis of water demand takes into water losses of 15% and 37%. The results of this study in 2031 SPAMDes Tirta Lestari can serve with a total of 85 home connections (SR) customers with a total water need of 0.32 liters / second (loss of 15%) and 0.37 liters / second (loss of 37%). The number of customers who can be served with a source water discharge of 0.89 liters / second is 109 SR (loss 15%) and 100 SR (loss 37%).